COVID-19 and change to home nursing care: Prospective study on 100 patients followed in CLCC - Despinasse, Marion; Schohn, Anna; Bimboes, Alexandre; Trensz, Philippe; Sirlin, Florian; Chiappa, Pascale; Frasie, Véronique (Bulletin du cancer, 2022)
During the COVID-19 epidemic, the lockdown measures were associated with professional guidelines to care for patients. We noticed that the home nursing care of some patients monitored in supportive care wards were interrupted. The aim of this study is to determine the impact of lockdown on the home nursing care of patients monitored in supportive care wards. This observational, descriptive, monocentric, and prospective study was conducted in the supportive care wards from the 04.20 to the 05.15.2020 among 100 patients. They were asked about their home nursing care and their frequency before and after lockdown. Our study received a favorable ruling from the ethics committee of the Hôpitaux universitaires de Strasbourg. About two thirds of patients had experienced a change with their home nursing care. A complete interruption was observed for 40% of them and a reduction of frequency for 10% of them. Some populations were more deeply affected: patients with a performance status 3-4, women, patients living alone or patients with motor disability. The interruption of a task usually performed by a professional was observed for 49% of patients, with the task becoming incumbent on the patient or family caregivers. Our study shows a strong impact of the lockdown on the home nursing care of our patients in spite of the professional guidelines encouraging continuity of care. Our study underlines the great importance of protecting the access to care of the most vulnerable patients.